2010
DOI: 10.2298/abs1002397k
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and antipyretic activities of Amaranthus viridis Linn. in different experimental models

Abstract: The methanolic extract of the whole plant extract of Amaranthus viridis L (MEAV) was screened for antinociceptive activity using the acetic acid writhing test, hot plate test and tail immersion test in mice and for antipyretic activity using the yeast-induced pyrexia method in rats, at doses of 200 and 400 mg/kg body weight. Significant (p<0.01) dose-dependent antinociceptive and antipyretic properties were observed with 200 and 400 mg/kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…The hot plate test described by Eddy and Leimback (1953) was used to assess the analgesic effects of fresh onion juice (Kumar et al, 2009). The animals were divided into six groups with eight mice in each.…”
Section: Hot Plate Methodsmentioning
confidence: 99%
“…The hot plate test described by Eddy and Leimback (1953) was used to assess the analgesic effects of fresh onion juice (Kumar et al, 2009). The animals were divided into six groups with eight mice in each.…”
Section: Hot Plate Methodsmentioning
confidence: 99%
“…The previous scientific studies have been reported that alkaloids, flavonoids and tannins are known to inhibit prostaglandin synthetase that is responsible for its antinociceptive and anti-inflammatory effects [31][32][33][34][35][36][37][38] . Therefore antinociceptive and anti-inflammatory effect of the extract may be due to the presence of flavonoids, tannins, and alkaloids either singly or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini juga mendukung penelitian sebelumnya yang membuktikan bahwa tanaman yang mengandung flavonoid memiliki efek antipiretik, seperti tanaman bayam duri (Kumar et al 2009), semak bunga putih (Owoyele et al 2008), umbi bawang merah (Setiyawan 2005), dan brotowali (Ernitawati 2004).…”
Section: Pembahasanunclassified